2018
DOI: 10.3390/ijgi7110433
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Water Hazard Zones: Mapping Intersecting Environmental Health Vulnerabilities and Polluter Disproportionality

Abstract: This study advanced a rigorous spatial analysis of surface water-related environmental health vulnerabilities in the California Bay-Delta region, USA, from 2000 to 2006. It constructed a novel hazard indicator—“impaired water hazard zones’’—from regulatory estimates of extensive non-point-source (NPS) and point-source surface water pollution, per section 303(d) of the U.S. Clean Water Act. Bivariate and global logistic regression (GLR) analyses examined how established predictors of surface water health-hazard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 82 publications
(254 reference statements)
2
17
0
Order By: Relevance
“…where log(P/1 − P) was the natural log of the P probability of an Oregon public high school holding an open campus policy in 2017, α was the intercept, and β k X k is the sum of β coefficients for the k number of X independent variables [66,67].…”
Section: Regression Methodologymentioning
confidence: 99%
“…where log(P/1 − P) was the natural log of the P probability of an Oregon public high school holding an open campus policy in 2017, α was the intercept, and β k X k is the sum of β coefficients for the k number of X independent variables [66,67].…”
Section: Regression Methodologymentioning
confidence: 99%
“…We used an established Bonferroni correction procedure in our assessment of the statistical significance of the Moran's I i results [72][73][74][75][76]. This procedure addresses concerns over abnormality, multiple comparisons, and spatial autocorrelation in the distribution of the standard normal variates (Z i ).…”
Section: Tract-level Univariate and Spatial Pattern Analysesmentioning
confidence: 99%
“…where v was the number of seemingly independent tests, r was the Moran's I for the OHAS household response rate or the prevalence of Latinx/Nonwhite householders across census tracts, and n was the number of tests [72][73][74][75][76]. We then divided the standard p-value of 0.05 by the number of seemingly independent tests to determine the FDR-corrected p-value for classifying the significance of the cluster/outlier results for the OHAS household response rate and the prevalence of Latinx/Nonwhite householders.…”
Section: Tract-level Univariate and Spatial Pattern Analysesmentioning
confidence: 99%
“…Noteworthy among its results, the study found that residence in primarily White neighborhoods correlated with lower PM 2.5 exposures, while residence in primarily Hispanic neighborhoods correlated with higher PM 2.5 exposures. More recently, a nationwide, longitudinal, multi-level study found that, when compared to Whites, Blacks and Hispanics/Latinos (hereafter referred to with the gender-neutral term, “Latinxs” [14]) experienced significantly higher levels of exposure to PM 2.5 concentrations from 1990 to 2009 in their census block of residence, net of other individual- and metropolitan-level factors [15].…”
Section: Introductionmentioning
confidence: 99%